Child Sexual Abuse Attributions: Are They Different Depending on Mothers versus Fathers’ Reactions? - Eunice Magalhães; Andreia Gomes; João Graça; Carla Antunes; Inês Chim; Célia Ferreira; Patrício Costa (Anuario de Psicología Jurídica)

(untitled)
Family reactions to child sexual abuse (CSA) are important, but there is a lack of research on the effect of maternal and paternal reactions on social attributions towards the victim and perpetrator. We conducted an experimental study (N = 549, aged 18-76) using vignettes in which the reactions of the mother or father (blame, denial, or support) were manipulated. Statistically significant differences were found for the blame scenario on victim culpability, meaning that participants reported greater victim culpability when the father blamed the victim than when the mother did so. The hypothesised moderating effect of empathy was not confirmed. The results also showed that younger participants tended to attribute greater seriousness to the assault, greater honesty and credibility to the victim, greater culpability to the perpetrator, and less culpability to the victim. Women reported higher levels of victim credibility than men. Furthermore, women and more educated participants reported lower levels of victim culpability and greater assault seriousness. Positive associations were also found between empathy and the perceived seriousness of the assault. The findings and discussion shed light on the differences in CSA attributions depending on mothers’ and fathers’ reactions.